BRAZIL (Fiep Bulletin - online, 2015)
In Brazil, when was here, JG Thulin, left, beyond the technical lessons offered to specialize in physical education, an impression of his outstanding personality. Gray hairs on the task of serving the physical education around the world, earned the right to rest. Eight decades overdue for permanent analysis of complex educational problems and significant successes in reaching initiatives assured him experience and authority to admirable lessons bonded in an extraordinary work of pioneering.